Learning Profile of Intellectually Disabled Students Using e-LAPD with Individualized Strategies Via Liveworksheet on Atomic Theories - Zelinda Fitri Amalia; Khurrotul Aini; Rahmania Fitrah Sari; Ima Kurrotun Ainin; Dian Novita (Jurnal Penelitian Pendidikan IPA, 2025)
The digitalization of chemistry education is crucial for ensuring inclusivity and equal learning opportunities, particularly for students with intellectual disabilities. This study investigated students’ functional learning profiles through digital student worksheets (e-LAPD) on atomic theories, integrated with individualized strategies based on Universal Design for Learning (UDL) via the Liveworksheet platform. A mixed-methods approach with a concurrent embedded design was applied, involving three students with intellectual disabilities at SMAN 10 Surabaya. Qualitative data were collected through semi-structured interviews and classroom observations, then thematically analyzed using NVivo 11, which yielded two major themes: the implementation of e-LAPD and students’ learning profiles. The analysis revealed that the implementation of e-LAPD effectively supported students’ understanding of the development of atomic theories, as evidenced by quantitative results obtained from questionnaire responses and pre-test/post-test instruments. Questionnaire data indicated that 100% of students reported improved conceptual understanding through e-LAPD. Furthermore, pre-test and post-test results showed a significant improvement with a high average N-gain score of 0.88. In addition, the findings highlighted students’ learning abilities and learning profiles, such as their tendency to engage with interactive visual media, their preference for verbal explanations, and their reliance on physical interaction during learning activities.